2021
DOI: 10.1029/2021gl094583
|View full text |Cite
|
Sign up to set email alerts
|

The Precipitated Electrons in the Region of Diffuse Aurora Driven by Ionosphere‐Thermosphere Collisional Processes

Abstract: Electron precipitation in the region of the diffuse aurora provides a noticeable amount of energy to the Ionosphere-Thermosphere (IT) system (e.g., Newell et al., 2009) and is the subject of debate in the recent experimental studies of this phenomena (Dombeck et al., 2018). It is generally assumed that either whistler mode chorus waves or Electrostatic electron Cyclotron Harmonic (ECH) waves are mostly responsible for the initiation of such electron precipitation to begin with, depending on the spatial locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…However, it has been found that the Maxwellian energy spectrum tends to underestimate the incident soft (0.1–1 keV) electrons and the difference of the 0.1 keV electrons can be up to 2–3 orders of magnitude (e.g., McGranaghan, Knipp, Matsuo, et al., 2015; McGranaghan, Knipp, Solomon, Fang, 2015; McIntosh & Anderson, 2014; Wing et al., 2019). Although modeling efforts have been made to incorporate additional types of energy spectra different from a Maxwellian energy spectrum in recently developed electron precipitation models (e.g., McGranaghan et al., 2016; Newell et al., 2009, 2014), soft electron precipitation may still be inaccurately represented (Khazanov et al., 2021; Wing et al., 2019). Since soft electron precipitation is an important ionization source in the F‐region ionosphere, the conductivity and Joule heating at F‐region altitudes may not be correctly estimated when the Maxwellian energy spectrum is used in GCMs (e.g., McGranaghan et al., 2016; Rees, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found that the Maxwellian energy spectrum tends to underestimate the incident soft (0.1–1 keV) electrons and the difference of the 0.1 keV electrons can be up to 2–3 orders of magnitude (e.g., McGranaghan, Knipp, Matsuo, et al., 2015; McGranaghan, Knipp, Solomon, Fang, 2015; McIntosh & Anderson, 2014; Wing et al., 2019). Although modeling efforts have been made to incorporate additional types of energy spectra different from a Maxwellian energy spectrum in recently developed electron precipitation models (e.g., McGranaghan et al., 2016; Newell et al., 2009, 2014), soft electron precipitation may still be inaccurately represented (Khazanov et al., 2021; Wing et al., 2019). Since soft electron precipitation is an important ionization source in the F‐region ionosphere, the conductivity and Joule heating at F‐region altitudes may not be correctly estimated when the Maxwellian energy spectrum is used in GCMs (e.g., McGranaghan et al., 2016; Rees, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the previous studies by Khazanov at al. (2017); Khazanov, Glocer, and Chu (2021); Khazanov, Shen, et al (2021), a STET code running configuration in the tilted dipole magnetic field is presented for the first time. Such an approach allows to take care of different realistic illumination conditions in the Northern and Southern Hemispheres that is an important element in the proper calculation of photoelectron fluxes.…”
Section: Simulation Of T1 and T2 Casesmentioning
confidence: 99%
“…It solves gyro-average kinetic equation for the suprathermal electrons (SE) for the energies above 1 eV and include relativistic effects (Khazanov, 2010). This kinetic equation for the SE can be presented as (Khazanov, Shen, et al, 2021, Khazanov, Glocer, & Chu, 2021)…”
Section: The Stet Codementioning
confidence: 99%
See 2 more Smart Citations